Evaluation of various antibiotics on growth rate and feed efficiency of finishing pigs - G L Allee; M Noll (Kansas Agricultural Experiment Station Research Reports, 1978)
We used 150 Yorkshire finishing pigs averaging 120 lbs initially to evaluate the following antibotics: Tylan, Stafac, Oleandomycin, and Flavomycin on rate and efficiency of gain. The trial ended when pigs within a replicate averaged approximately 220 lbs. There were no significant differences in rate or efficiency of gain by pigs fed nonmedicated or medicated diets.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Antibiotics; Growth rate; Feed Efficiency; Finishing pigs